Argument estimates of certain multivalent functions involving a linear operator - Nak Eun Cho; J. Patel; G. P. Mohapatra (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to derive some argument properties of certain multivalent functions in the open unit disk involving a linear operator. We also investigate their integral preserving property in a sector.